THE RELATIONSHIP BETWEEN PEERS AND NUMERICAL ABILITY WITH STUDENT LEARNING OUTCOMES CLASS XI IPA - Kartika Kusuma Maharany; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This study aims to determine whether or not a positive and significant relationship between peers and numerical ability with the results of mathematics learning students of class XI IPA State Senior High School 1 Girimulyo (SMA Negeri 1 Girimulyo) Kulon Progo District odd Semester of the academic year 2017/2018. The population used in this study is all students of class XI IPA odd Semester SMA Negeri 1 Girimulyo Kulon Progo regency academic year 2017/2018, which amounts to 46 students and is divided into two classes. Sampling class using a random sampling technique to the class, so that I obtained class XI IPA 2 as class trial and class XI Science class 1(IPA 1) as a research class. Data collection techniques used questionnaires and tests. The data collection instrument uses peer questionnaires, numerical ability tests, and mathematics learning outcomes. The instrument test analysis uses validity, a test of different power, and a reliability test. Test prerequisite analysis using normality test, independent test, linearity test. Data analysis using simple correlation analysis and multiple regression analysis. Â The results showed that there was a positive and significant relationship between peers and numerical ability with mathematics learning result with multiple regression equation Å¶ = -16,723 + 0,428Xâ‚ + 0,632Xâ‚‚ and double correlation coefficient (R) equal to 0,628, and obtained Fcount = 6,824 and Ftabel = 3.47, so Fcount> Ftable. The relative contribution (Xâ‚) = 46,281% and (Xâ‚‚) = 53,719% with double determination coefficient 0,394 and effective contribution (Xâ‚) = 18,230% and (Xâ‚‚)=21,160%.